Violence Attribution Errors Among Low-Risk and High-Risk Offenders - Waytowich, Vicki (2009)
Juvenile offenders have numerous factors that contribute to their delinquency, including family dysfunction, drug and alcohol abuse, negative peer influences, and social cognitive development. One area of social cognitive development linked to deviant behavior is attributional biases. Based on the prior research of Daley and Onwuegbuzie (2004), the purpose of the present concurrent mixed methods study was to explore the differences in the frequency of violence attribution errors among juvenile delinquents; the extent that peer-victimization, self-esteem, and demographic variables predict violence attribution errors among juveniles; and the differences in the types of violence attribution errors between incarcerated (high-risk) and probation (low-risk) juvenile delinquents. The results indicated juvenile offenders made violence attribution errors more than 50% of the time when evaluating the behavior of others, suggesting that the low-risk offenders are at major risk of committing high-risk offenses in the future. The results of the multiple regression analysis indicated that 5 variables (i.e., attitude towards the violent acts of others, verbal victimization, attacks on property, social relationships, and morals) statistically predicted the number of violence attribution errors a youth made (F [21, 88] = 2.28,p = .004). Further, with regard to the typology of reasons for violence attributions, the same 7 emergent themes were extracted for all 3 offender samples: self-control, violation of rights, provocation, irresponsibility, poor judgment, fate, and conflict resolution. Findings are discussed relative to the literature on attributional bias and offender behavior